Documenting the Literature of Teachers’ Leadership Values - Cris Kuntadi; Eric Hermawan; Antoni Ludfi Arifin; Antaiwan Bowo Pranogyo (AL-ISHLAH: Jurnal Pendidikan, 2023)
The aim of this study is to conduct a literature review related to the values of a teacher's leadership grounded on six aspects, namely focus, open-mindedness, respect, doing the best, being excellent, and integrity. This literature study employed a digital literature search to obtain the data. Some selection criteria were considered such as the published articles from 2010 – 2020. From the selection, 10 articles were gathered and analyzed using content analysis. The analysis results informed that teacher's leadership is not only task and people-oriented, but also focuses on transforming a teacher into a leader who values attention, openness, respect, does the best, be excellent, and has integrity. Teachers must learn to focus on themselves and to achieve this a leader must concentrate on one thing. Teachers as leaders with open-minded or open-minded values can help a teacher grow into better person. A teacher with respect values is someone who treats everyone with the same respect regardless of rank or status. The teacher as a leader who does his best at work is the mentality of a good and exemplary leader. The real professional integrity of a teacher consists of characteristics such as being trustworthy, honest, and sincere at work.